The Effectiveness of ASEAN-PAC in Regional Corruption Prevention: A Literature Review - Hanif Arsa Mahdiya; Nailatul Ulyaa; Aryasatya Abhinaya Bintang; Rafandra Patria Sebayang; Nareswari Pallanda Surubeng; Jihan nisrina (Journal of Human Interaction and Social Studies, 2026)
Corruption in Southeast Asia has evolved into a transnational challenge that increasingly requires collective responses beyond national jurisdictions. This study aims to examine the effectiveness of the ASEAN Parties Against Corruption (ASEAN-PAC) in supporting regional corruption prevention and anti-corruption cooperation within ASEAN. The research employs a qualitative literature review approach based on academic journal articles, legal studies, policy reports, and institutional publications related to regional anti-corruption governance. Data were analyzed using qualitative content analysis and thematic synthesis to identify patterns concerning ASEAN-PAC’s achievements, limitations, and future prospects. The findings indicate that ASEAN-PAC has contributed significantly to strengthening institutional communication, information sharing, capacity-building initiatives, and the diffusion of anti-corruption norms among member states. However, its operational effectiveness remains constrained by the non-interference principle, the non-binding nature of regional commitments, legal fragmentation, and disparities in domestic institutional capacity. These factors limit the organization’s ability to support stronger enforcement mechanisms, particularly in cross-border investigations and asset recovery efforts. The study concludes that ASEAN-PAC remains an important regional platform but requires deeper legal cooperation, enhanced institutional capacity, and stronger governance standards to improve its effectiveness in addressing transnational corruption challenges in Southeast Asia.